APPLICATION OF CONSTRUCTIVISM THEORY OF COOPERATIVE LEARNING MODEL IN LEARNING - Putri Rahmayanti; Neviyarni; Herman Nirwana (Yayasan Citra Dharma Cindekia, 2021)
Learning is a process carried out to change behavior carried out by the learning process. To create a learning process that can be applied and assist students in learning is to use constructivist theory. Constructivistic theory is a learning theory that builds students' thinking and understanding to make it easier to understand learning. One of the models that can be applied is using constructivist theory, one of which is the cooperative learning model. This model involves actively being able to develop oneself and involves good social relations and social interactions in the classroom to create good effectiveness in the classroom. The purpose of this research is to obtain new information and understanding so that it can be applied in the learning process. The research methodology used is a literature study. Based on this research, it is understood that constructivist theory with cooperative learning model is considered appropriate to be applied in learning to achieve learning objectives.